(untitled) (Journal of Oriental Studies, 2021)
The development of modern China, the growth of its economic power and the strengthening of its influence in the international arena cannot be separated from the leadership of the CCP. To some extent, Xi Jinping’s rise to power marks the beginning of a “new era.” Xi Jinping was guided by the slogan of “comprehensive deepening and acceleration of reforms.” In the introduction to the Constitution of the concepts of state structure of the People’s Republic of China, Xi Jinping’s “guiding ideas” were added to the contributions of Mao Zedong and Deng Xiaoping. The article examines the evolution of the formation of the CCP’s power doctrine under the leadership of Xi Jinping, as well as the basic concepts and principles. The main aspects of the theory of “socialism with Chinese characteristics in a new era” and the ideas of Xi Jinping are analyzed, new features of socialism and the innovative path of China, the ideology of classical Marxism are analyzed. At the same time, China’s strategic domestic and foreign policy is aimed at realizing the “Great Renaissance of the Chinese Nation” and “China Dream” through the implementation of ideological and economic mega-projects that contribute to the global process. This topic is one of the most relevant today. Therefore, the main purpose of this article is to reveal the doctrine of Xi Jinping’s rule. Key words: Xi Jinping, XIX Congress of the Communist Party, Socialism with Chinese features in a new era, great revival, Chinese dream.